Structural insights into diversity and n-alkane biodegradation mechanisms of alkane hydroxylases - Ji, Yurui; Mao, Guannan; Wang, Yingying; Bartlam, Mark (Frontiers in Microbiology, 2013)
Environmental microbes utilize four degradation pathways for the oxidation of n-alkanes. Although the enzymes degrading n-alkanes in different microbes may vary, enzymes functioning in the first step in the aerobic degradation of alkanes all belong to the alkane hydroxylases. Alkane hydroxylases are a class of enzymes that insert oxygen atoms derived from molecular oxygen into different sites of the alkane terminus (or termini) depending on the type of enzymes. In this review, we summarize the different types of alkane hydroxylases, their degrading steps and compare typical enzymes from various classes with regard to their three dimensional structures, in order to provide insights into how the enzymes mediate their different roles in the degradation of n-alkanes and what determines their different substrate ranges. Through the above analyses, the degrading mechanisms of enzymes can be elucidated and molecular biological methods can be utilized to expand their catalytic roles in the petrochemical industry or in bioremediation of oil-contaminated environments.